Comparison of two algorithms for automatic model calibration - von Klaus Eckhardt (Hydrologie und Wasserbewirtschaftung, 2002)
Calibration of a model allows to reduce parameter uncertainty and therefore uncertainty in simulation results. Complex models can be automatically calibrated by means of stochastic global optimization algorithms. Two of these algorithms are compared: on the one hand the Boender-Timmer-Rinooy Kan (BTRK) algorithm, a multistart algorithm with previous clustering, and on the other hand the Shuffled Complex Evolution (SCE) algorithm, a genetic algorithm. The algorithms are applied to an analytic distributed model used to simulate water balance and transport processes in meso- to macroscale catchments, the version SWAT-G of the Soil and Water Assessment Tool (SWAT). The SCE algorithm proves to be superior to the BTRK algorithm. A high model efficiency is obtained.Original Abstract: Die Kalibrierung eines Modells ermoeglicht eine Reduzierung der Parameterunsicherheit und damit der Unsicherheit in Simulationsergebnissen. Komplexe Modelle koennen mittels stochastischer globaler Optimierungsalgorithmen automatisch kalibriert werden. Zwei dieser Algorithmen werden hinsichtlich ihrer Leistungsfaehigkeit miteinander verglichen: einerseits der Boender-Timmer-Rinooy Kan (BTRK) Algorithmus, ein Multistart-Algorithmus mit vorhergehender Clusterung, und andererseits der Shuffled Complex Evolution (SCE) Algorithmus, ein Genetischer Algorithmus. Die beiden Algorithmen werden auf ein analytisches verteiltes Modell zur Nachbildung des Wasser- und Stoffhaushalts in meso- bis makroskaligen Einzugsgebieten oberirdischer Gewaesser angewendet, die Version SWAT-G des Soil and Water Assessment Tool (SWAT). Der SCE Algorithmus erweist sich dem BTRK Algorithmus als ueberlegen. Es wird eine hohe Guete der Modellanpassung erreicht.